Balance documental sobre emprendimiento social en el contexto rural (2020)
Social entrepreneurship is a relatively new issue that has been gaining importance over the past few years, due to its significant contribution in developing countries and the transformation of rural space. The method of study was qualitative, based on national and international documents, where it was possible to highlight all the barriers that rural women face in order to develop their ventures (funding difficulties, gender inequity, discrimination, lack of knowledge and studies), and which characteristics can help them with their empowerment. Finally, it is concluded that the origin of the entrepreneurship in them, arises as a need to be empowered through economic remuneration and / or recognition by its space.